Specializing When It Counts: Comparing the Dose-Time Effect of Distance Variety between Swimming and Track Running - Dennis-Peter Born; Jesús J. Ruiz-Navarro; Jenny Lorentzen; Glenn Björklund (MDPI AG, 2024)
Objective: To conduct a longitudinal retrospective analysis, explore the relationship between success at peak performance age and the number of different race distances athletes competed in each year (within-sport distance variety), and compare the dose-time effect of this distance variety throughout the development process between male swimmers and track runners. Methodology: Male swimmers (n = 6033) and track runners (n = 19,278) still competing at peak performance age were ranked, and the number of different race distances was extracted retrospectively for each year until early junior age (13-14-year-old category) from the databases of the European Aquatics and World Athletics federations. Firstly, correlation analysis determined the relationship between ranking at peak performance age and distance variety. Secondly, Poisson distribution provided the probability and dose-time effect of distance variety for becoming an international-class athlete at peak performance age. Results: Generally, correlation analysis revealed low coefficients (r ≤ 0.22) but significant effects (p < 0.001) for larger distance variety and success at peak performance age. Poisson distribution revealed the highest probability of becoming an international-class swimmer when competing in 2-4 race distances at junior age, depending on the primary race distance. The dose-time effect indicated a gradual reduction in the number of race distances as athletes approached peak performance age, narrowing down to 1-2, 2-3, and 3-4 distances for sprint, middle-, and long-distance races, respectively. Track runners exhibited a lower distance variety than swimmers, with a consistent optimum of 1-2 race distances across the age groups. Conclusions: The present findings including data of the most combined race distances for each primary race distance and a comparison between swimming and track running provide new background information to challenge traditional training regimes and help establish new strategies for long-term athlete development.